BoCS: Image Retrieval Using Explicable Methods - Silva, Endi D. C.; Traina, Agma J. M. (Anais da Conference on Graphics, Patterns and Images (SIBGRAPI); 2023: Anais da XXXVI Conference on Graphics, Patterns and Images, 2023)
In recent years, image generation has been growing at a very fast pace, demanding specific systems for managing large image datasets. For example, we can mention the content-based image retrieval (CBIR) systems. Usually, they use a representation of feature vectors based on the images' visual content to store/retrieve them and to perform demanded queries. Currently, neural networks perform the task of generating image representations with great mastery. However, these networks usually create methods that are difficult to understand or to explain, which for some applications, such as medical decisionmaking systems, can be a significant disadvantage. Thinking about the explainability aspect, in this work, we present a new technique based on the bag of visual words (BoVW) which, in addition to generating promising explainable methods, has long been the state of the art for generating image representations. The results showed that the presented method BoCS overcomes similar methods and still has the potential to be further explored.